1990
DOI: 10.1111/j.1439-037x.1990.tb00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Seed Yield and Quality Characters of Four Spring Oil Rapeseed Cultivars as Influenced by Population Arrangements and Densities

Abstract: Variations of yield and quality characters of four spring oilseed rape cultivars (B. napus L.) arranged in 16 or 32 cm between drills and under three population densities (30, 60 and 90 plants/nr) were investigated in a split‐plot design with three replications in 1986 and 1987 in West Germany. Cultivar Callypso gave the highest seed and oil yields per plot and the highest seed index, harvest index and seed yield/main stem, per branches and per plant. Differences due to arrangements were significant in 1986 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 2 publications
1
6
1
1
Order By: Relevance
“…Correlation dependence of total protein content and density (r=-0.06) and genotype (r=0.09) was not confirmed by correlation analysis, while among total protein content and production year (r=-0.58*) a significant negative correlation ratio was obtained (Table 2). Our studies failed to confirm the influence of genotype on protein content determined by Marinković et al (2010), while Shrief et al (1990) determined higher protein content in seed obtained at higher density. Negative correlation ration between protein content and oil was determined by Hao et al (2004), which was confirmed by our investigation.…”
Section: Resultscontrasting
confidence: 94%
“…Correlation dependence of total protein content and density (r=-0.06) and genotype (r=0.09) was not confirmed by correlation analysis, while among total protein content and production year (r=-0.58*) a significant negative correlation ratio was obtained (Table 2). Our studies failed to confirm the influence of genotype on protein content determined by Marinković et al (2010), while Shrief et al (1990) determined higher protein content in seed obtained at higher density. Negative correlation ration between protein content and oil was determined by Hao et al (2004), which was confirmed by our investigation.…”
Section: Resultscontrasting
confidence: 94%
“…Morrison et al (1990); Leach et al (1999); Farsak (2009); Farsak and Kaynak (2010) indicated in their studies the oil ratio was not affected by inter-row spacing was consistent with our study results. Shrief et al (1990) found that the high density created high values in oil yield; Chauhan et al (1992) and Oad et al (2001) found that broad inter-row spaces created the highest oil ratio was incompatibility with our result results.…”
Section: Oil Ratiosupporting
confidence: 67%
“…This result concurs with the findings of Kondra (1977) and Van Deynze et al (1992), who reported that protein content did not change with varying plant densities. However, Shrief et al (1990) reported that protein content was higher under higher population densities.…”
Section: Seed Protein Contentmentioning
confidence: 93%